2014
DOI: 10.3945/ajcn.114.083766
|View full text |Cite
|
Sign up to set email alerts
|

The double burden of undernutrition and excess body weight in Ecuador

Abstract: This article shows the coexistence of high rates of undernutrition and OW/OB at the individual, household, and national levels in Ecuador. Although integrated approaches to address the emerging double burden are required, public health policies to date have not responded adequately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 19 publications
5
135
1
13
Order By: Relevance
“…In fact nutritional transition of populations, especially a greater consumption of refined carbohydrates and fat, has consistently resulted in increased frequency and severity of obesity and its comorbidities in all populations in the world including, as above mentioned, in subjects with LS and similar conditions in other latitudes [1]. Thus it is possible that components of the metabolic syndrome, including insulin resistance and diabetes could appear in the Ecuadorian GHRD population, along with the present westernization of the diet in Southern Ecuador and the increasing numbers of subjects -non GHRD-who develop diabetes in this region [9].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…In fact nutritional transition of populations, especially a greater consumption of refined carbohydrates and fat, has consistently resulted in increased frequency and severity of obesity and its comorbidities in all populations in the world including, as above mentioned, in subjects with LS and similar conditions in other latitudes [1]. Thus it is possible that components of the metabolic syndrome, including insulin resistance and diabetes could appear in the Ecuadorian GHRD population, along with the present westernization of the diet in Southern Ecuador and the increasing numbers of subjects -non GHRD-who develop diabetes in this region [9].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…A brief overview of the studies' characteristics is presented in Table 2, and some important features are described in the following sections. Eight articles provided a general review [ [35][36][37][38][39][40][41][42], and 2 examined the DBMN situation in Africa [43,44].…”
Section: Published Studies Examining Dbmn In Developing Countriesmentioning
confidence: 99%
“…Several studies have also demonstrated association of undernutrition with obesity, microelements deficiency, anemia, hypertension, high rate of infectious and parasitic diseases among children and adolescents in developing countries (5)(6)(7)9).…”
Section: Discussionmentioning
confidence: 99%
“…Unbalanced nutrition is also associated with loss of ability to work and have unfavorable dynamics leading to loss of health and significantly contributing to demographic problems, affecting mostly people of work age. In children and adolescents, malnutrition is one of the causes of high cardiovascular and noninfectious diseases mortality (5)(6)(7)(8)(9). According to recent data, malnutrition affected about 165 million children of age < 5 years old, was responsible for 45% of total mortality in this population (10,11).…”
Section: Introductionmentioning
confidence: 99%